Placing the social economy - Amin, Ash.; Cameron, Angus, 1965-; Hudson, Ray, 1948- (London ; New York : Routledge, 2002)
This book provides an account of real life experience in a social economy. It focus themes as, the range of academic and policy expectation that have emerged in recent years in the developed world; the policies of New Labour in Britain; the dynamics of social enterprises in Bristol, London, Middlesbrough and Glasgow; These critical assessments lead the authors to reflect in the future potential of the social economy and the possible policy changes that are necessary to maximise whatever opportunity the sector provides.
Includes bibliographical references (p. [136]-142) and index.
lje 15/01/14
Loans
Keywords: Human services -- Contracting out -- Great Britain; Social service -- Contracting out -- Great Britain; Mixed economy -- Great Britain; Great Britain -- Social policy -- 1979-